Optimalisasi Informasi Citra T1 W1 Post-Contrast Dengan Fat Saturation dan Pengaturan Time Repetition: Studi pada Pemeriksaan Magnetic Resonance Imaging Brain dengan Kasus Tumor - Akhmad Haris Sulistiyadi; Ari Suwondo; Sugiyanto Sugiyanto (Poltekkes Kemenkes Semarang, 2015)
Background: Fat saturation is an alternative technique to improve image information in T1 WI post contrast MRI of brain tumor. It can increase lesion conspituity by suppressing normal tissue’s signal. To optimize image information by using fat saturation, selection of Fat Saturation type and Time Repetition (TR) value are important.Objectives: to analyze the differences in T1 WI post-contrast image information in MRI of brain tumor in various type of Fat Saturation and TR value.Methods: Experimental study with factorial design conducted in Telogorejo Hospital-Semarang. Nine combinations (9 groups) of three Fat Saturation types (none, weak, and strong) by three TR values (700 ms, 750 ms, and 800 ms) were given to 12 patients of MRI brain tumor. Image informations were assessed by measuring SNR (white matter, gray matter, lesions, surrounding tissue), CNR (white matter- gray matter, white matter-CSF, gray matter-CSF, lesion- surrounding tissue), lesion conspituity, artifacts, and contrast image in general.Results: The results showed that there were significant differences in SNR of white matter, gray matter, and in surrounding tissue (p 0.05); CNR of white matter-CSF, gray matter-CSF, lesion-tissue surrounding tissue (p 0.05); and lesion conspituity (p 0.05) between groups with no sat fat, weak fat sat, and strong fat sat. There were significant differences in SNR of white matter, gray matter, and surrounding tissue (p 0.05); and CNR of white matter-CSF, gray matter-CSF, and lesion- surrounding tissue (p 0.05) between group TR 700 ms, TR 750 ms, and TR 800 ms.Conclusion: Combination of strong fat saturation and TR 700 ms can produce the most optimal image information.